Riqueza, prestigio y ofrenda divina: los usos del cacao en el mundo nahua. - Strong Zúñiga, Alexandra (Hospitalidad ESDAI)
Through an exhaustive documental revision of primary and secondary sources it was possible to attain the main purpose of this article: to reconstruct the attitudes that the Nahuatl speaking peoples had towards cacao before the arrival of the Spaniards. By using this methodology it was possible to conclude that cacao occupied a central place in the social, religious and economic dynamics of a part of the pre-Columbian world. The facts gathered from these sources may help the Mexican tourism industry in two ways. First, providing a solid base for the development of a rich culture of gastronomichistoric tourism in places such as Chiapas and Tabasco, and, in second place, highlighting the importance that this ingredient, now so ubiquitous in international culinary traditions, has for the ancestral culture of Mexico. In this sense, with the help of the abundant tourist attractions that Mexico already offers, cacao may become living history.